The use of 4,4,4-trifluorothreonine to stabilize extended peptide structures and mimic β-strands - Xu, Yaochun; Correia, Isabelle; Ha-Duong, Tap; Kihal, Nadjib; Soulier, Jean-Louis; Kaffy, Julia; Crousse, Benoît; Lequin, Olivier; Ongeri, Sandrine (Beilstein Journal of Organic Chemistry, 2017)
Pentapeptides having the sequence R-HN-Ala-Val-X-Val-Leu-OMe, where the central residue X is L-serine, L-threonine, (2S,3R)-L-CF3-threonine and (2S,3S)-L-CF3-threonine were prepared. The capacity of (2S,3S)- and (2S,3R)-CF3-threonine analogues to stabilize an extended structure when introduced in the central position of pentapeptides is demonstrated by NMR conformational studies and molecular dynamics simulations. CF3-threonine containing pentapeptides are more prone to mimic β-strands than their natural Ser and Thr pentapeptide analogues. The proof of concept that these fluorinated β-strand mimics are able to disrupt protein–protein interactions involving β-sheet structures is provided. The CF3-threonine containing pentapeptides interact with the amyloid peptide Aβ1-42 in order to reduce the protein–protein interactions mediating its aggregation process.
Keywords: aggregation; beta-sheet; fluorine; peptide; unnatural amino acid

(untitled) - Zhou, Y.; Wang, J.; Gu, Z.; Wang, S.; Zhu, W.; Aceña, J. L.; Soloshonok, V. A.; Izawa, K.; Liu, H. (Chem. Rev., 2016)

(untitled) - Uhlig, T.; Kyprianou, T.; Martinelli, F. G.; Oppici, C. A.; Heiligers, D.; Hills, D.; Calvo, X. R.; Verhaert, P. (EuPa Open Proteomics, 2014)

(untitled) - Buer, B. C.; Marsh, E. N. G. (Protein Sci., 2012)

(untitled) - Marsh, E. N. G. (Acc. Chem. Res., 2014)

(untitled) - Meng, H.; Kumar, K. (J. Am. Chem. Soc., 2007)

(untitled) - Zanda, M. (New J. Chem., 2004)

(untitled) - Kitamoto, T.; Marubayashi, S.; Yamazaki, T. (Tetrahedron, 2008)

(untitled) - Vulpetti, A.; Dalvit, C. (Drug Discovery Today, 2012)

(untitled) - Salwiczek, M.; Nyakatura, E. K.; Gerling, U. I.; Ye, S.; Koksch, B. (Chem. Soc. Rev., 2012)

(untitled) - Kitamoto, T.; Marubayashi, S.; Yamazaki, T. (Chem. Lett., 2006)

(untitled) - Pelay-Gimeno, M.; Glas, A.; Koch, O.; Grossmann, T. N. (Angew. Chem., Int. Ed., 2015)

(untitled) - Watkins, A. M.; Arora, P. S. (ACS Chem. Biol., 2014)

(untitled) - Milroy, L.-G.; Grossmann, T. N.; Hennig, S.; Brunsveld, L.; Ottmann, C. (Chem. Rev., 2014)

(untitled) - Cheng, P.-N.; Liu, C.; Zhao, M.; Eisenberg, D.; Nowick, J. S. (Nat. Chem., 2012)

(untitled) - Kaffy, J.; Brinet, D.; Soulier, J.-L.; Correia, I.; Tonali, N.; Fera, K. F.; Iacone, Y.; Hoffmann, A. R. F.; Khemtémourian, L.; Crousse, B.; Taylor, M.; Allsop, D.; et al. (J. Med. Chem., 2016)

(untitled) - Jiang, Z.-X.; Qin, Y.-Y.; Qing, F.-L. (J. Org. Chem., 2003)

(untitled) - Zeng, C.-m.; Kerrigan, S. A.; Katzenellenbogen, J. A.; Slocum, C.; Gallacher, K.; Shomali, M.; Lyttle, C. R.; Hattersley, G.; Miller, C. P. (Tetrahedron Lett., 2010)

(untitled) - Qing, F.-L.; Pen, S.; Hu, C.-M. (J. Fluorine Chem., 1998)

(untitled) - Soloshonok, V. A.; Kukhar, V. P.; Galushko, S. V.; Svistunova, N. Yu.; Avilov, D. V.; Kuz'mina, N. A.; Raevski, N. I.; Struchkov, Y. T.; Pysarevsky, A. P.; Belokon, Y. N. (J. Chem. Soc., Perkin Trans. 1, 1993)

(untitled) - Kitazume, T.; Lin, J. T.; Yamazaki, T. (Tetrahedron: Asymmetry, 1991)

(untitled) - Scolastico, C.; Conca, E.; Prati, L.; Guanti, G.; Banfi, L.; Berti, A.; Farina, P.; Valcavi, U. (Synthesis, 1985)

(untitled) - Sting, A. R.; Seebach, D. (Tetrahedron, 1996)

(untitled) - Belokon, Y. N.; Tararov, V. I.; Maleev, V. I.; Savel'eva, T. F.; Ryzhov, M. G. (Tetrahedron: Asymmetry, 1998)

(untitled) - Soloshonok, V. A.; Avilov, D. V.; Kukhar, V. P.; Tararov, V. I.; Savel'eva, T. F.; Churkina, T. D.; Ikonnikov, N. S.; Kochetkov, K. A.; Orlova, S. A.; Pysarevsky, A. P.; Struchkov, Y. T.; Raevsky, N. I.; et al. (Tetrahedron: Asymmetry, 1995)

(untitled) - Marcovici-Mizrahi, D.; Gottlieb, H. E.; Marks, V.; Nudelman, A. (J. Org. Chem., 1996)

(untitled) - Szilagyi, L.; Jardetzky, O. (J. Magn. Reson., 1989)

(untitled) - Spera, S.; Bax, A. (J. Am. Chem. Soc., 1991)

(untitled) - Wishart, D. S.; Sykes, B. D. (Methods Enzymol., 1994)

(untitled) - Wishart, D. S.; Sykes, B. D. (J. Biomol. NMR, 1994)

(untitled) - Wishart, D. S.; Bigam, G. C.; Holm, A.; Hodges, R. S.; Sykes, B. D. (J. Biomol. NMR, 1995)

(untitled) - Smith, L. J.; Fiebig, K. M.; Schwalbe, H.; Dobson, C. M. (Folding Des., 1996)

(untitled) - Vuister, G. W.; Bax, A. (J. Am. Chem. Soc., 1993)

(untitled) - Avbelj, F.; Grdadolnik, S. G.; Grdadolnik, J.; Baldwin, R. L. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Schmidt, J. M. (J. Biomol. NMR, 2007)

(untitled) - Ohnishi, M.; Urry, D. W. (Biochem. Biophys. Res. Commun., 1969)

(untitled) - Kopple, K. D.; Onishi, M.; Go, A. (J. Am. Chem. Soc., 1969)

(untitled) - Cierpicki, T.; Otlewski, J. (J. Biomol. NMR, 2001)

(untitled) - Minor, D. L., Jr; Kim, P. S. (Nature, 1994)

(untitled) - Pellegrino, S.; Tonali, N.; Erba, E.; Kaffy, J.; Taverna, M.; Contini, A.; Taylor, M.; Allsop, D.; Gelmi, M. L.; Ongeri, S. (Chem. Sci., 2017)

(untitled) - Kaffy, J.; Brinet, D.; Soulier, J.-L.; Khemtémourian, L.; Lequin, O.; Taverna, M.; Crousse, B.; Ongeri, S. (Eur. J. Med. Chem., 2014)

(untitled) - Vahdati, L.; Kaffy, J.; Brinet, D.; Bernadat, G.; Correia, I.; Panzeri, S.; Fanelli, R.; Lequin, O.; Taverna, M.; Ongeri, S.; Piarulli, U. (Eur. J. Org. Chem., 2017)

(untitled) - LeVine, H., III (Methods Enzymol., 1999)